MATEC Web of Conferences - Bolgova; Larionov specialist in the field of power engineering technician of Tomsk Polytechnic University; Zenkov engineer at Tomsk Polytechnic University, assistant specialist in the field of power engineering; Yankovsky specialist in the field of power engineering Associate Professor, Researcher of Tomsk Polytechnic University, Candidate of Technical Sciences (EDP Sciences, 2018)
The process of coal oxidation with applied Cu(СH[3]COO)[2] additive was studied by the capillary incipient wetness impregnation method with 5% mass concentration. The experiment was conducted by thermogravimetric analysis at a heating rate of 2.5C/min to a maximum temperature of 600C in atmospheric air. It was established that application of the initiation additive leads to a significant reduction in the initial temperature of sublimation and active oxidation of volatile compounds ([tau]Ti=78C) and the oxidation end temperature ([tau]T[f]=64C). It was established that in the presence of copper acetate the nature of coal oxidation reaction significantly changes (DTG data). The parameters of the coals oxidation process in the presence of copper acetate were determined, and an assumption was made about the presence of a composite catalytic effect.